Analiza efektywności zarządzania nieruchomością - Nalepka, Adam; Łach, Katarzyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper focuses on the purpose, scope, and principles of application of economic analysis in real estate management effectiveness. Real estate management is interpreted as the decision making process referring to real estate and actions undertaken to maintain, exploit, and supply real estate. Each property that is managed should be treated as separate profit centre. Economic analysis aimed at management effectiveness evaluation investigates the value or the level of selected economic indexes describing management process and estimates economic-financial coefficients. The evaluation consists in comparison of the level of estimated indexes and coefficients with their model or required value. In case of divergence between model and calculated values, the question should be answered: "What should be changed in hitherto applied real estate management process, to improve effectiveness?". (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 308-319